Exploring Cyber Sexual Harassment of Queer Students in Indian Universities: Prevalence, Impact, and Institutional Responses - Chakraborty, Swati; Lata, Parvesh (Journal of Neonatal Surgery, 2025)
Digital spaces have become crucial arenas for identity exploration and community-building among queer students in Indian universities. However, they are also sites of increased vulnerability, exposing queer individuals to cyber sexual harassment and identity-based discrimination. This study examines the prevalence, nature, and impact of such harassment, using empirical data gathered as part of a larger PhD research project. The work aims to amplify the voices of queer students by focussing on their lived experiences in order to better understand how online harassment affects their academic, emotional, and social lives. The study uncovers patterns of targeted cyber violence, appearance-based harassment, and queerphobic trolling on platforms such as Instagram, WhatsApp, and dating apps. The emotional toll is significant: participants report anxiety, digital withdrawal, and academic disengagement, often compounded by the fear of being outed or further marginalised. The paper also identifies critical institutional and policy gaps. Existing university mechanisms, such as POSH committees, largely fail to recognize or address queer-specific and cyber-based harassment. Many students avoid reporting due to a lack of trust in these systems, absence of trained staff, and no clear protocols for digital abuse. This paper highlights the limitations of existing support systems and the urgent need for inclusive, intersectional, and cyber-aware policies. Recommendations include faculty sensitization, queer-inclusive policy reforms, anonymous reporting tools, and the creation of safer digital and physical spaces within campuses. Addressing these challenges is essential to ensuring that higher education environments in India are genuinely safe and inclusive for queer students.